Uses and Limitations of Quantitative Research in English Language Education - Khatri, Krishna Kumar; Karki, Debraj (Bouddhik Abhiyan (बौद्धिक अभियान), 2022)
This paper is an attempt to provide insights on quantitative research in general and the uses and limitations of quantitative research in the field of English language education in particular. The paper aims to present and discuss the uses and limitations of quantitative research in the area of English language education. Building upon the literature related to the topic, the paper begins with the background of research in general. Then, it introduces the quantitative research as an important research approach in social sciences. More importantly, it presents and discusses the major areas of uses and limitations of quantitative research in the field of English education. Finally, the paper is concluded with the idea that quantitative research approach is significantly used to address the issues of English language education along with other research approaches in terms of nature and contexts of the research phenomena.